Development and validation of cardiac patient competence questionnaire, Iranian version - Roohafza, Hamidreza (ARYA Atheroscler, 2015)
BACKGROUND: The aim was to translate and develop a patient competence (PC) questionnaire in the context of cardiology and test its validity and reliability. METHODS: In total, 148 cardiac patients who have inclusion criteria of the study were completed cardiac PC (CPC) questionnaire. Hospital Anxiety and Depression Scale and self-administered instrument European quality of life 5-dimensions were used to further validate the CPC questionnaire. The CPC was translated according to the recommended methodology for translating questionnaires, and psychometric properties including internal consistency, factor analysis, discriminant validity, construct validity, and concurrent criterion validity were tested. RESULTS: Five domains in problem-focused task including search for information, self-regulation, being assertive, independent decision-making, and looking for social services, and three domains in emotion-focused task including stress management, confronting the threat, and avoidance were obtained by factor analysis. The standardized Cronbach’s α of all domains were statistically significant (P < 0.001) and internal consistency for all domains was acceptable. Significant intercorrelations of CPC domains also indicated good criterion validity. As there were no cross-loadings, the domains have demonstrated good construct validity and discriminant validity. CONCLUSION: The results of this study show that the Persian version of the CPC is a reliable and valid questionnaire. Although further improvement of this measure is clearly required, it suggests being a potential basis for investigating the determinants and health effects of CPC.